Study on aerodynamic characteristics of Proton Waja by using CFD [compact disc] - 201740 Lee, Wei Jin (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2006